A deterministic evaluation of heat stress mitigation and feed cost under climate change within the smallholder dairy sector. (28th December 2016) - York, L.; Heffernan, C.; Rymer, C.; Panda, N.
Abstract : In the global South, dairying is often promoted as a means of poverty alleviation. Yet, under conditions of climate warming, little is known regarding the ability of small-scale dairy producers to maintain production and/or the robustness of possible adaptation options in meeting the challenges presented, particularly heat stress. The authors created a simple, deterministic model to explore the influence of breed and heat stress relief options on smallholder dairy farmers in Odisha, India. Breeds included indigenous Indian (non-descript), low-grade Jersey crossbreed and high-grade Jersey crossbreed. Relief strategies included providing shade, fanning and bathing. The impact of predicted critical global climate parameters, a 2°C and 4°C temperature rise were explored. A feed price scenario was modelled to illustrate the importance of feed in impact estimation. Feed costs were increased by 10% to 30%. Across the simulations, high-grade Jersey crossbreeds maintained higher milk yields, despite being the most sensitive to the negative effects of temperature. Low-capital relief strategies were the most effective at reducing heat stress impacts on household income. However, as feed costs increased the lower-grade Jersey crossbreed became the most profitable breed. The high-grade Jersey crossbreed was only marginally (4.64%) more profitable than the indigenous breed. The results demonstrate the importance of understanding the factors and practical trade-offs that underpin adaptation. The model also highlights the need for hot-climate dairying projects and programmes to consider animal genetic resources alongside environmentally sustainable adaptation measures for greatest poverty impact.